Calbindin D 28k expression and abscence of apoptosis in the cerebellum of Solanum bonariense L intoxicated bovines - Verdes, José Manuel (2010)
Solanum bonariense intoxication is characterized by cerebellar neuronal vacuolation, degeneration and necrosis. Cerebellar Purkinje cells seem especially susceptible but more research is needed to determine the pathogenesis of neuronal necrosis and mechanism of Purkinje cell susceptibility. Calbindin D 28k (CbD28k) is highly expressed in Purkinje cells, and it has been used as a specific marker of normal and degenerative Purkinje cells. The goals of the present work were to further describe S.bonariense induced disease by describing Purkinje cell specific degenerative changes using CbD28k expression correlated with the apoptotic changes determined using TUNEL and ultrastructural changes. Both dose and duration of S. bonariense intoxication decrease the number of Purkinje cells in all the studied areas. CbD28k immunohistochemistry was an excellent marker of Purkinje cells as immunoreactivity did not change in normal tissues or degenerative tissues. This suggests that rapid neuronal degeneration and death is not induced by excessive calcium excitatory stimulation. As found in previous studies, TUNEL tests and electron microscopy suggest Purkinje cell degeneration and death is not occurring via an apoptotic process. In summary these findings suggest that S.bonariense poisoning induces progressive Purkinje cell death that is not mediated by excitotoxicity or apoptotic activation.Solanum bonariense intoxication is characterized by cerebellar neuronal vacuolation, degeneration and necrosis. Cerebellar Purkinje cells seem especially susceptible but more research is needed to determine the pathogenesis of neuronal necrosis and mechanism of Purkinje cell susceptibility. Calbindin D 28k (CbD28k) is highly expressed in Purkinje cells, and it has been used as a specific marker of normal and degenerative Purkinje cells. The goals of the present work were to further describe S.bonariense induced disease by describing Purkinje cell specific degenerative changes using CbD28k expression correlated with the apoptotic changes determined using TUNEL and ultrastructural changes. Both dose and duration of S. bonariense intoxication decrease the number of Purkinje cells in all the studied areas. CbD28k immunohistochemistry was an excellent marker of Purkinje cells as immunoreactivity did not change in normal tissues or degenerative tissues. This suggests that rapid neuronal degeneration and death is not induced by excessive calcium excitatory stimulation. As found in previous studies, TUNEL tests and electron microscopy suggest Purkinje cell degeneration and death is not occurring via an apoptotic process. In summary these findings suggest that S.bonariense poisoning induces progressive Purkinje cell death that is not mediated by excitotoxicity or apoptotic activation.